Pengaruh Kebijakan Try Out Terhadap Prestasi Siswa Dalam Mata Pelajaran Kimia Kelas XII IPA Di SMAN 1 Talibura - Sunarwin Sunarwin; Ichsan Anshory (Jurnal Kebijakan dan Pengembangan Pendidikan, 2016)
Abstract: This study aims to analyze the effect of the tryout policy on student achievement in chemistry class XII Science at SMAN 1 Talibura. The data collection method uses a documentation study with a try out as an independent variable and national exam as the dependent variable. The population is Talibura State High School, students. The research sample included all students of class XII Science. Test the validity of the instrument using the Spearman-Brown formula and reliability using the Alpha formula from Cronbach, and fulfilling valid and reliable requirements. Hypothesis testing uses the formula of normality, linearity, simple linear regression, F test, and t-test. The results obtained a probability value of 0.016 ≤ 0.05 and the results of the analysis where the significance is constant 0,000 <0.05 and the significance of Try out are 0.033 <0.05 so it can be concluded that the tryout variable is significantly correlated with the national examination variable. Testing the effect of Try Out on chemistry learning outcomes obtained a constant T count of 6.351 and Try out 2.167 is greater than the T-table (1.9853) then H0 is rejected and H1 is accepted. While the value of F-count = 5.892 <F-table, then H0 is rejected and H1 is accepted. The ability of the Try Out variable in explaining the variance of the National Examination variable is 4.7% (R-Square) so it can be concluded that the influence of the Try Out variable on the National Examination variable is very small.Keywords: Try Out, Student Achievement, Subject of  Chemistry Abstrak: Penelitian ini bertujuan untuk menganalisis pengaruh kebijakan try out terhadap prestasi siswa dalam mata pelajaran kimia kelas XII IPA di SMAN 1 Talibura. Metode pengumpulan data menggunakan studi dokumentasi dengan try out sebagai variabel independen dan ujian nasional sebagai variabel dependen. Populasi adalah siswa Sekolah Menengah Atas Negeri 1 Talibura. Sampel penelitian meliputi semua siswa kelas XII IPA. Uji instrument validitas menggunakan rumus Spearman Brown dan reliabilitas menggunakan rumus Alpha dari Cronbach, dan memenuhi syarat valid dan reliabel. Uji hipotesis menggunakan rumus normalitas, linieritas, regresi linier sederhana, uji F, dan uji t. Hasil penelitian didapatkan nilai probabilitas sebesar 0,016 ≤ 0,05 dan pada hasil analisis dimana signifikansi constant 0,000 < 0,05 dan signifikansi Try out 0,033 < 0,05 sehingga dapat disimpulkan bahwa variabel try out berkorelasi signifikan terhadap variabel ujian nasional. Pengujian pengaruh Try Out terhadap hasil belajar kimia diperoleh T hitung constant 6,351 dan Try out 2,167 lebih besar dari T - table (1,9853) maka H0 ditolak dan H1 diterima. Sedangkan nilai F-hitung = 5,892 < F-tabel, maka H0 ditolak dan H1 diterima. Kemampuan variabel Try Out dalam menjelaskan varians dari variabel Ujian Nasional adalah sebesar 4,7 % (R-Square) sehingga dapat disimpulkan pengaruh variabel Try Out terhadap variabel Ujian Nasional sangat kecil.Kata kunci: Try Out, Prestasi siswa, Mata Pelajaran Kimia